2020
DOI: 10.24940/ijird/2020/v9/i12/dec20029
|View full text |Cite
|
Sign up to set email alerts
|

Age and Job Satisfaction among Public Secondary School Teachers in Nakuru County, Kenya

Abstract: IntroductionJob satisfaction and motivation are very crucial to the long-term growth of any educational system around the world. As Ololube (2006) points out, job satisfaction is important in the same way as professional knowledge, teaching skills, and access to educational resources. This, as Patrick ( 2007) points out, is due to the strong link between job satisfaction and academic achievement of students. A satisfied teacher has a friendly attitude and greater enthusiasm which contributes immensely towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…Several studies obtained related results, indicating that female teachers’ job satisfaction levels were higher than male teachers’ (Shaukat et al, 2019 ; Toropova et al, 2021 ). However, in some studies, gender was not effective on teachers’ job satisfaction levels (Crossman and Harris, 2006 ; Shrestha, 2019 ; Singh and Kumar, 2016 ), while in some others, contrarily to our research findings, male teachers had higher job satisfaction levels (Chitra, 2020 ; Maina et al, 2021 ). The research results indicated that private school teachers’ job satisfaction levels were lower than public-school teachers’.…”
Section: Conclusion and Discussioncontrasting
confidence: 58%
“…Several studies obtained related results, indicating that female teachers’ job satisfaction levels were higher than male teachers’ (Shaukat et al, 2019 ; Toropova et al, 2021 ). However, in some studies, gender was not effective on teachers’ job satisfaction levels (Crossman and Harris, 2006 ; Shrestha, 2019 ; Singh and Kumar, 2016 ), while in some others, contrarily to our research findings, male teachers had higher job satisfaction levels (Chitra, 2020 ; Maina et al, 2021 ). The research results indicated that private school teachers’ job satisfaction levels were lower than public-school teachers’.…”
Section: Conclusion and Discussioncontrasting
confidence: 58%